Puberty and Plexiform Neurofibroma Tumor Growth in Patients with Neurofibromatosis Type I - Dagalakis, Urania (2013)
OBJECTIVE: To assess the relationship between pubertal progression and change in PN burden over time in pediatric and young adult patients with neurofibromatosis type 1 (NF1) and plexiform neurofibromas (PN). STUDY DESIGN: Analyses accounted for sex, age, race, and chemotherapy. Forty-one patients with NF1 (15 female, 26 male) were studied at the National Cancer Institute (NCI). Tanner stage, testosterone, progesterone, estradiol, insulin-like growth factor −1, luteinizing hormone, and follicle stimulating hormone were assessed. Tumor volume was measured using Magnetic Resonance Imaging and lesion detection software developed at NIH. Patients were divided into two groups based upon whether they were actively progressing through puberty (n=16) or peri pubertal (n=25), and were followed for an average of 20 months. Tumor growth rates in the puberty and peri pubertal group were analyzed for a subset of patients. RESULTS: There was no statistically significant difference in tumor burden change over time (cc/kg/month) between the pubertal and peri pubertal group (−0.16 ± 0.34 vs. 0.03 ± 1.8, p=0.31), and in the PN growth rates pre and during puberty (p=0.90). Change in tumor volume/patient weight/time did not correlate with testosterone change/time in males or estradiol change/time in females. CONCLUSION: These findings support that hormonal changes of puberty do not accelerate PN growth. Additional long-term follow up of patients is necessary to further characterize the interaction between puberty and tumor growth.